Theory and Experimental Study of Corona Initial E-Field Strength of HVDC Large Fittings. Issue 1 (January 2021) - Shiling, Zhang
Abstract: The electrode were used to imitate the valve tower shield plate, grading ring, grading ball and grading shield for UHVDC valve hall. Uneven electric field of the irregular conductor can not be calculated theoretically or measured accurately. The variation of typical electrode corona inception electric field strength is analyzed and threshold value of the corona inception electric field of the valve hall fittings is acquired. With the adequate modification, limited electric field magnitude for the valve hall is proposed. With the gray system MGM (1, M) model fitting and predicting technology, the E-field strength single-point high-precision measurement and the the wide-area time interval corona initial E-field fitting and predicting operation can be realized. The experimental results show that the maximum error is 3.25% within the measured concentration range, which increases with applied voltage. The maximum RSD% is less than 2.7%, showing the good stability. This system can provide the novel method for the study of corona detection of large fittings in UHVDC valve hall.